Konsistensi aparat pengawasan internal pemerintah (APIP) untuk meningkatkan kualitas laporan keuangan Provinsi Gorontalo - Agussalim, Alfiyah; Handayani, Dwi Nur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Regional Government Financial Report is a form of government accountability to the community in the form of the Regional Revenue and Expenditure Budget (APBD). Financial reports made by local governments must be of high quality and in accordance with standards. For this reason, APIP is needed to oversee the activities or programs of the local government so that the program runs according to its objectives. This study aims to describe the consistency of the Government Internal Supervisory Apparatus (APIP) to improve the quality of the Gorontalo provincial government's financial reports. The focus of this research is audit, review, evaluation, monitoring and other supervisory activities.The sampling technique was carried out by purposive sampling and the informants in this study were the Inspectorate of the Gorontalo Province Inspectorate and several related work units at the Gorontalo Provincial Inspectorate. The data collection techniques used are observation, interview, and documentation techniques. The data obtained were analyzed through the stages of data collection, data presentation and drawing conclusions. From the results of the study, it can be concluded that with the consistency and APIP can realize government accountability and quality Local Government Financial Reports.